(untitled) (Plant Tissue Culture and Biotechnology, 2016)
The anther culture response in Solanum commersonii (2n = 2x = 24, 1EBN) and S. chacoense (2n = 2x = 24, 2EBN), two wild potato germplasm resources was studied to obtain haploid plants. Three accessions from each of the two species and 3200 anthers from each genotype were cultured. Authors assessed different culture media; ascorbic acid, L?cysteine and silver nitrate (AgNO3) were included to prevent browning of anther cultures. Addition of AgNO3, was effective to induce embryogenesis. The clones from S. commersonii showed different embryogenic response to androgenesis. However, the three accessions from S. chacoense did not induce any embryo in the same conditions. Ploidy level of the regenerated clones was estimated by flow cytometry and confirmed by chromosome counts. This is the first report of haploid plants obtained from anther culture in S. commersonii, with important implications in sequencing efforts and potato breeding. Plant Tissue Cult. & Biotech. 26(2): 159-173, 2016 (December)